Improving the climate signal of tree-ring blue intensity of sub-fossil wood using hydrogen peroxide: An example from the gulf of Alaska, USA - Wenshuo Zhao; Junpeng Fu; Nick Wiesenberg; Benjamin V. Gaglioti; Gregory C. Wiles (Dendrochronologia, 2025)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Detection and attribution of an anomaly in terrestrial photosynthesis in Europe during the COVID-19 lockdown - Angela Che Ing Tang; Christophe R. Flechard; Nicola Arriga; Dario Papale; Paul C. Stoy; Nina Buchmann; Matthias Cuntz; John Douros; Silvano Fares; Alexander Knohl; Ladislav Šigut; Guillaume Simioni; et al. (Science of The Total Environment, 2023)

Aspirin use and prostate tumor angiogenesis - Benjamin C. Fu; Kai Wang; Lorelei A. Mucci; Steven K. Clinton; Edward L. Giovannucci (Cancer Causes & Control, 2022)

Maximum carbon uptake rate dominates the interannual variability of global net ecosystem exchange - Zheng Fu; Paul C. Stoy; Benjamin Poulter; Tobias Gerken; Zhen Zhang; Guta Wakbulcho; Shuli Niu (Global Change Biology, 2019)
Terrestrial ecosystems contribute most of the interannual variability (IAV) in atmospheric carbon dioxide (CO 2 ) concentrations, but processes driving the IAV of net ecosystem CO 2 exchange (NEE) remain elusive. For a predictive understanding of the global C cycle, it is imperative to identify indicators associated with ecological processes that determine the IAV of NEE. Here, we decompose the annual NEE of global terrestrial ecosystems into their phenological and physiological components, namely maximum carbon uptake (MCU) and release (MCR), the carbon uptake period (CUP), and two parameters, α and β, that describe the ratio between actual versus hypothetical maximum C sink and source, respectively. Using long‐term observed NEE from 66 eddy covariance sites and global products derived from FLUXNET observations, we found that the IAV of NEE is determined predominately by MCU at the global scale, which explains 48% of the IAV of NEE on average while α, CUP, β, and MCR explain 14%, 25%, 2%, and 8%, respectively. These patterns differ in water‐limited ecosystems versus temperature‐ and radiation‐limited ecosystems; 31% of the IAV of NEE is determined by the IAV of CUP in water‐limited ecosystems, and 60% of the IAV of NEE is determined by the IAV of MCU in temperature‐ and radiation‐limited ecosystems. The Lund‐Potsdam‐Jena (LPJ) model and the Multi‐scale Synthesis and Terrestrial Model Inter‐comparison Project (MsTMIP) models underestimate the contribution of MCU to the IAV of NEE by about 18% on average, and overestimate the contribution of CUP by about 25%. This study provides a new perspective on the proximate causes of the IAV of NEE, which suggest that capturing the variability of MCU is critical for modeling the IAV of NEE across most of the global land surface.

Interannual variability of ecosystem carbon exchange: From observation to prediction - Shuli Niu; Zheng Fu; Yiqi Luo; Paul C. Stoy; Trevor F. Keenan; Benjamin Poulter; Leiming Zhang; Shilong Piao; Xuhui Zhou; Han Zheng; Jiayin Han; Qiufeng Wang; et al. (Global Ecology and Biogeography, 2017)
Aim Terrestrial ecosystems have sequestered, on average, the equivalent of 30% of anthropogenic carbon (C) emissions during the past decades, but annual sequestration varies from year to year. For effective C management, it is imperative to develop a predictive understanding of the interannual variability (IAV) of terrestrial net ecosystem C exchange (NEE). Location Global terrestrial ecosystems. Methods We conducted a comprehensive review to examine the IAV of NEE at global, regional and ecosystem scales. Then we outlined a conceptual framework for understanding how anomalies in climate factors impact ecological processes of C cycling and thus influence the IAV of NEE through biogeochemical regulation. Results The phenomenon of IAV in land NEE has been ubiquitously observed at global, regional and ecosystem scales. Global IAV is often attributable to either tropical or semi‐arid regions, or to some combination thereof, which is still under debate. Previous studies focus on identifying climate factors as driving forces of IAV, whereas biological mechanisms underlying the IAV of ecosystem NEE are less clear. We found that climate anomalies affect the IAV of NEE primarily through their differential impacts on ecosystem C uptake and respiration. Moreover, recent studies suggest that the carbon uptake period makes less contribution than the carbon uptake amplitude to IAV in NEE. Although land models incorporate most processes underlying IAV, their efficacy to predict the IAV in NEE remains low. Main conclusions To improve our ability to predict future IAV of the terrestrial C cycle, we have to understand biological mechanisms through which anomalies in climate factors cause the IAV of NEE. Future research needs to pay more attention not only to the differential effects of climate anomalies on photosynthesis and respiration but also to the relative importance of the C uptake period and amplitude in causing the IAV of NEE. Ultimately, we need multiple independent approaches, such as benchmark analysis, data assimilation and time‐series statistics, to integrate data, modelling frameworks and theory to improve our ability to predict future IAV in the terrestrial C cycle.

A Systematic Assessment of the Use of Platelet-Rich Plasma in Spinal Fusion - Benjamin D. Elder; Christina Holmes; C. Rory Goodwin; Sheng-Fu Lo; Varun Puvanesarajah; Thomas A. Kosztowski; John E. Locke; Timothy F. Witham (Annals of Biomedical Engineering, 2015)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Development of delivery methods for carbohydrate-based drugs: controlled release of biologically-active short chain fatty acid-hexosamine analogs - Udayanath Aich; M. Adam Meledeo; Srinivasa-Gopalan Sampathkumar; Jie Fu; Mark B. Jones; Christopher A. Weier; Sung Yun Chung; Benjamin C. Tang; Ming Yang; Justin Hanes; Kevin J. Yarema (Glycoconjugate Journal, 2010)